Outcome of orthodontic mini-implant loss in relation to interleukin 6 polymorphisms. Issue 5 (May 2016) - Reichow, A.M.; Melo, A.C.; de Souza, C.M.; Castilhos, B.B.; Olandoski, M.; Alvim-Pereira, C.C.K.; Alvim-Pereira, F.; Trevilatto, P.C.
Abstract: Mini-implants (MIs) are used increasingly for orthodontic anchorage and their success may require some osseointegration, which is affected by the underlying host immune-inflammatory response. Interleukin 6 (IL-6) is a cytokine expressed during the host response after a trauma or infection. The aim of this study was to investigate the association of clinical characteristics and IL6 tag single nucleotide polymorphisms (which capture the information of the whole gene in terms of genetic variability) with the loss of MIs for orthodontic anchorage. A total of 487 patients were treated with orthodontic MIs between 2004 and 2010. After the application of inclusion and exclusion criteria, the sample comprised 104 patients with one or more MIs that had been in function for at least 6 months with no loss, and 31 patients who had lost one or more MIs. Allele A of rs2069843 and allele T of rs2069849 were suggestively associated with the loss of MIs for orthodontic anchorage and were in complete linkage disequilibrium, which means that one of them is sufficient to capture the same information. The location of installation (mandible) and the number of MIs installed per patient were also associated with the loss of MIs.